Re-dating Zhoukoudian Upper Cave, northern China and its regional significance. Issue 121 (August 2018) - Li, Feng; Bae, Christopher J.; Ramsey, Christopher B.; Chen, Fuyou; Gao, Xing
Abstract: Due to the presence of multiple partial modern human skeletons thought to have been interred along with a diversity of evidence of symbolic behavior, Zhoukoudian Upper Cave (ZKD UC; formally "Choukoutien") from northern China has long been a critical site for understanding Late Quaternary human evolution and particularly the role eastern Asia played. Unfortunately, uncertainty regarding ZKD UC's chronology has long hindered determination of its importance in the debate over modern human origins. This situation has been particularly problematic because dates from the primary archaeological layers of ZKD UC have ranged from the Late Pleistocene to the Early Holocene (∼34–10 ka), with clearly different implications depending on which age is used. Here, we present a new set of accelerator mass spectrometry radiocarbon dating results from ZKD UC. Based on this new set of dates and further re-evaluations of the previous dating analyses, archaeological materials, published excavation reports and stratigraphy, we conclude that the ZKD UC archaeological layers minimally date to 35.1–33.5 ka. Given the similarities between the human fossils and archaeology between ZKD UC and western Eurasia, it is likely that the ZKD UC human foragers were part of dispersal events across northern Eurasia toward Siberia and eventually reaching into northern China.